STUDY OF NUTRITIONAL STATUS APPLICATION DEVELOPMENT IN CORRECTIONAL ASSISTED CITIZENS (WBP) AT LAPAS NARKOTIKA KELAS IIA MUARA BELITI - Master Srowi; Hartati Hartati; Ahmad Richard Victorian (Universitas Negeri Medan, 2023)
This research is entitled The study of the development of nutritional status applications in inmates penitentiary (wbp) in Class IIa Prison Narcotics Muara Beliti. The purpose of the research This is to determine the nutritional status of the food consumed by the inmates penitentiary (wbp) in Class IIa Prison Narcotics Muara Beliti. This research using research and development methods, according to Borg and Gall quoted by (Sari, Farida, & Syazali, 2016) research and development is a process used to develop products such as software (devices software) Computers in the form of applications. So, it can be concluded research and Development is a process in creating new products as well as new products developing and validating an existing product. Meanwhile according to (Putra, 2013) Research And Development is a research method that intentionally, systematically, aiming/directed to find, formulate, improve, develop, produce, test the effectiveness of products, models, methods/strategies/methods, services, certain procedures that are superior, new, effective, efficient,productive and meaningful. From the results of anthropometric measurements which include age, height and weight, from 100 inmates who were sampled or the subject of this study, the results can already be stated to meet nutritional standards balanced .. The implications expected from this research prison managers can concerned about the quality of the food they will eat.